Identifikasi Morfologi lalat Buah Bactrocera spp. (Diptera :Tephritidae) di Kabupaten Minahasa (JURNAL ENFIT : Entomologi dan Fitopatologi, 2019)
The many types of fruit flies and the presence of vague traits between species cause identification and characteristics of these insects often encounter difficulties. Â The problem of how the morphological character of the fruit fly Bactrocera spp. can be determined to the species level precisely and accurately. The purpose of this research is to study and identify the types of fruit flies Bactrocera spp. based on morphological characters. The identification stage is carried out by determining the morphological characteristics of the head, thorax, wings and abdomen for each species of Bactrocera spp. The results of identification of several species of fruit flies Bactrocera to the level of species based on morphological characteristics of adult insects found five species of Bactrocera are Bactrocera umbrosa (Fabricius), Bactrocera albistrigata (de Meijere), Bactrocera carambolae (Drew and Hancock), Bactrocera dorsalis (Hendel), and Bactrocera tau (Walker).